Utilizing Reverse Axillary Mapping in the Surgical Treatment of Axillary Hidradenitis Suppurativa: A Novel Approach - Rafal R. Iskanderian, MBChB, MRCSI, CABS; Fatima Al Khyeli, MD; Ahmed Ali, MD; Raffi Gurunian, MD, FACS (Plastic and Reconstructive Surgery, Global Open)
Summary:. Hidradenitis suppurativa (HS) is a chronic inflammatory cutaneous disease that imposes a surgical challenge and mandates radical, full-thickness excision of involved skin to achieve remission. Upper limb lymphedema can be a complication of HS chronic infection or radical surgery due to the violation of lymphatics. Reverse axillary mapping (RAM) was developed to reduce upper limb lymphedema after axillary surgery for breast cancer. We aim to demonstrate a novel approach by utilizing RAM during radical excision of axillary HS in 2 cases treated at Cleveland Clinic Abu Dhabi. By injecting isosulfan blue dye in the upper inner arm before surgery and observing the dye to map the lymphatic ducts, we clearly identified the blue lymphatic ducts in the surgical field and successfully preserved the dyed ducts while performing radical excision for axillary HS. In this report, we demonstrated the use of RAM in 2 patients with Hurley stage 3 axillary HS undergoing radical excisions. Identification of upper limb lymphatics with the aid of RAM was easy and instrumental in preventing damage to these ducts. Short-term follow-up did not show evidence of lymphedema or relapse of HS. The RAM technique enabled clear visualization of the lymphatic ducts located in our surgery field and prevented any possible lymphatic system damage in our cases. We suggest that RAM may be used as a routine in the surgical treatment of HS as well as in the popular bromhidrosis surgery to reduce the possibility of postsurgery upper limb lymphedema.